The role of different types of dopants in 1.3 μm InAs/GaAs quantum-dot lasers. (26th May 2022) - Deng, Huiwen; Jarvis, Lydia; Li, Zhibo; Liu, Zizhuo; Tang, Mingchu; Li, Keshuang; Yang, Junjie; Maglio, Benjamin; Shutts, Samuel; Yu, Jiawang; Wang, Lingfang; Chen, Siming; et al.
Abstract: The performance of O-band InAs/GaAs quantum-dot (QD) lasers grown by molecular beam epitaxy with three different doping strategies in the active region are investigated for a temperature range of 17 °C–97 °C. The lasing performance indicates that the n-type doping technique reduced the threshold current density of InAs QD lasers across the full temperature range and narrowed the near field lasing spot. However, for short-cavity lasers, the n-type doped laser switches from ground-state to excited-state lasing at a lower temperature compared to undoped and p-type modulation-doped lasers. In contrast, the p-type modulation-doped lasers have a reduced threshold current density for higher temperatures and for shorter lasers with cavity lengths of 1 mm and below.